KEPRIBADIAN BIG FIVE DAN STRATEGI REGULASI EMOSI IBU ANAK ADHD (ATTENTION DEFICIT HYPERACTIVITY DISORDER) - Listyanti Widuri, Erlina (Universitas Ahmad Dahlan, 2010)
This research was to examine a model of emotion regulation strategy on mothers of ADHD children, if big five personalities have a role on emotion regulation strategy. Quantitative analysis was carried out using AMOS 4.0 software, besides applying observation and interview. Nineteen patients of